Impact of COVID-19 on HIV services and anticipated benefits of vaccination in restoring HIV services in Ethiopia: A qualitative assessment - Amhare, Abebe Feyissa; Zhao, Min; Seeley, Janet; Zhang, Wei Hong; Goyomsa, Girma Garedew; Geleta, Tinsae Abeya; Zhao, Rui; Zhang, Lei (Frontiers in Public Health, 2022)
Background: HIV services are inevitably disrupted and affected due to COVID-19. There are many challenges in implementing appropriate HIV services, particularly in the provision of health care and the link between people living with HIV/AIDS and care retention. The study investigated the impact of COVID-19 on HIV services and the anticipated benefit of the COVID-19 vaccination on HIV service restoration in North Shewa, Oromia, Ethiopia. Methods: A qualitative descriptive study approach was used to explore how healthcare delivery evolved during the outbreak of COVID-19 in Ethiopia. Sixteen antiretroviral therapy (ART) clinics were selected from 13 districts and one administrative town in Ethiopia. From them, 32 ART providers were purposively selected based on their experience in ART provision. Data were collected from June to July 2021 using in-depth interviews. A thematic analysis approach was used to analyze the data, based on themes and subthemes emerging from the data. ATLAS.ti software was used for coding. Results: Healthcare for people living with HIV was interrupted due to the COVID-19 pandemic. Medical appointments, HIV testing and counseling services, opportunistic infection treatment, medicine supply, and routine tests viral load and CD4 T-cell count tests were interrupted. Due to short of healthcare staff, outreach testing services and home index testing were discontinued and HIV testing was limited only to hospitals and health centers. This has substantially affected accessibility to HIV testing and reduced the quality of HIV service delivery. Telehealth and less frequent visits to health facilities were used as alternative ways of delivering HIV services. The COVID-19 vaccination campaign is expected to restore healthcare services. Vaccination may also increase the confidence of healthcare providers by changing their attitudes towards COVID-19. Conclusions: The COVID-19 pandemic has substantially impacted the HIV service schedule and reduced the quality of HIV care in Ethiopia. Health facilities could not provide sufficient routine HIV services as they prioritize the fight against COVID-19, leading to an increase in service discontinuation, poor patient adherence and treatment failure.